Self-Sampling for Cervical Cancer: a Scoping Review - Murthi, Aditya Krishna; Kurniawan, Yani; Yunitra, Imelda; Halim, Catherine; Sisca, Sisca (CV. Publikasi Indonesia, 2025)
Cervical cancer remains a major global health concern, particularly in low- and middle-income countries (LMICs), where barriers such as limited healthcare access, cultural stigma, and logistical challenges hinder routine screening. Human papillomavirus (HPV) self-sampling has emerged as a promising alternative to clinician-collected sampling, offering the potential to improve screening coverage and reduce the burden of cervical cancer. This scoping review aims to synthesize current evidence on the feasibility, effectiveness, and acceptability of HPV self-sampling, with a focus on its impact on screening uptake, psychological outcomes, and diagnostic accuracy. Following the PRISMA-ScR guidelines, a systematic search was conducted across PubMed, Google Scholar, and Scopus, resulting in the inclusion of five studies: four randomized controlled trials and one umbrella review. Findings indicate that self-sampling reduces anxiety associated with cervical screening, improves participation among underserved populations, and demonstrates high diagnostic concordance with clinician-collected samples. Behavioral interventions, such as pay-it-forward models, show potential to enhance sample return and feedback rates. However, challenges remain regarding effective triage strategies for HPV-positive cases, especially in resource-limited settings. The review supports the integration of self-sampling into national screening programs, emphasizing the need for culturally tailored approaches and continued research on cost-effective triage methods.